The Differences in Body Image in terms of Gender, Cultural Background, and Students Admission Path - Yuca, Verlanda; Zahri, Triave Nuzila; Magistarina, Elrisfa (International Journal of Research in Counseling and Education, 2020)
As a part of physiological needs, human physical appearance is considered an essential part of people's lives. That integral part determines the formation of body image in the community. Body image is a mental picture of the body state. The development of student body image is not well-formed, so that it affects their life. In the lecture process, students tend to be inactive and have low self-esteem, which impact student life. Some factors that affect the body image are gender, cultural background, and the admission way. This study aims to describe the body image in terms of gender, cultural background, student's admission way, and the group's interaction. This study used a descriptive comparative method with 600 samples—the data collection using Yuca Puji Body-Image Inventory (YPBI) and ANOVA as an analyzing tool. The result shows significant differences in body image in terms of gender, cultural background, and admission. The results of this research can prove that student can develop body image in a positive direction. This result of the study will be used as a basic concept to determine a body image module.